The Tale of the Edible Cutlery - Das, Sanghamitra (AMC Indian Journal of Entrepreneurship, 2020)
This case throws light on the extensive revolutionary efforts undertaken by Narayana Peesapaty, a former scientist from International Water Management Institute, who left his comfortable job in pursuit for an alternative to plastic cutlery. He was deeply troubled by the extensive use of plastic cutlery knowing the fact that it has toxic effects on human beings as well as on the environment. As a result of his quest for replacing plastic cutlery he came up with edible cutlery. Peesapaty proved that through meticulous exploration, productive entrepreneurship, far-sightedness and creative imagination, it was possible to deal with social, economical, and environmental challenges. The case highlights the hurdles faced and the sacrifices done by Narayana Peesapaty for this nova satus.